IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL MELALUI DEBAT TERHADAP PEMAHAMAN KONSEP DAN BERPIKIR KRITIS PADA PERKULIAHAN TEORI AKUNTANSI - Sulastri, Andi; Amar, syahrul (Universitas Hamzanwadi, 2015)
The study aims to determine the effect of contextual learning through debate on the understanding of concepts and critical thinking skills in Accounting Theory lectures. With contextual learning through debates the students are able to: 1) Acquire knowledge and analyze problems, issues that are hot are contextually related to the concept in the theory of accounting, 2) Think critically and logically, and 3) Generate creative ideas clear and systematic as well as issued an opinion in discussions with a clear concept with broad-minded critical thinking about the Theory of Accounting. Quasi-experimental research methods with non equivalent control group design. The research design used Post-Test Only Control Group Design. IV semester student study sample that administer accounting theory courses in the academic year 2014/2015 . Instruments used: 1). Syllabus, SAP and textbooks, 2). Test understanding of concepts and critical thinking skills. Test Hipotesis1 and 2 used Independent Sample T-Test, the PC SPSS 16.0 for windows.uji Hypothesis 3 used test Manova. From the results of hypothesis testing, the significance level of 5% (1.232 <2.000), which means that Ho received, meaning there is no difference H1 understanding of the concept among the students who follow contextual learning through debate and students who attend the Learning Conventionally, while H 2: With t = 5.297, the significant level of 5% (5.297> 2.000) which means Ha accepted, meaning Differences in Thinking Skills Critical significant Among students who attend Contextual learning through debate and students who followed the conventional learning. And 3 simultaneously using current hypothesis test obtained Multivariate statistical values Pillai's Trace, Wilk's lambda, Hotelling's Trace, and Roy's Largest Root each with F = 14.304 with significance = 0.00. so it can be concluded that the adoption of Contextual learning through debate there is a significant impact on the understanding of concepts and Critical Thinking Skills students.Keywords: Contextual learning, debate, understanding of concepts and critical thinking skills